Lifetime Estimation of Welded Joints - Lagoda, Tadeusz (Springer Berlin Heidelberg : Imprint: Springer, 2008)
In the paper the author attempts to assess the fatigue life of chosen welded joints. It focuses especially on chosen problems that accompany deter- nation of the fatigue life of welded joints, taking into consideration the strain energy density parameter. Chapter 2 describes the welded joint as a stress concentrator. The state of stress and strain in the notch are described and theoretical and fatigue coefficients are indicated. The fatigue coef- cient of the notch effect is estimated on the basis of fictitious radius in the notch root. Chapter 3 presents a model of fatigue life assessment under uniaxial stress state with statistical handling of data presented. The new energy model of fatigue life assessment, which rests upon the analysis of stress and strain in the critical plane, is described in detail in chapter 4. The principle of such a description is presented in the uniaxial as well as in - axial state of loading. Chapter 5 contains the analysis of tests of four ma- rials subjected to different loadings: cyclic, variable-amplitude with Ga- sian distribution, and variable amplitude with Gaussian distribution and overloading for symmetric and pulsating loading. The analysis is based on the determined fatigue characteristics for all the considered materials. Chapter 6 shows the application of the model in the fatigue life assessment in the complex state of loading (bending with torsion of flange-tube and tube-tube joints) based on fatigue research of steel and aluminum welded joints carried out in well-known German centres.